2018
DOI: 10.1007/s10554-018-1352-y
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular ultrasound assessment of the effects of rotational atherectomy in calcified coronary artery lesions

Abstract: We sought to clarify intravascular ultrasound (IVUS) features of rotational atherectomy (RA) of calcified lesions. IVUS was performed post-RA and post-stent in 38 lesions and analyzed every 1 mm. Pre-intervention IVUS was performed when the IVUS catheter crossed the lesion (n = 11). Calcium Index was average calcium angle multiplied by calcium length. We compared lowest (n = 13), middle (n = 13), and highest (n = 12) Calcium Index tertiles. Reverberations (multiple reflections from calcium) with a concave-shap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Second, our results may be useful for establishing an educational program for junior RA operators. Because many literatures regarding RA and imaging devices have been published 1,[3][4][5][6][7][8][9][10] , even junior RA operators may be able to select an appropriate burr size, RotaWire, and RA strategy as long as an imaging device can cross the lesion before RA. However, as we shown here, there were many lesions that an IVUS catheter cannot cross, and the incidence of slow flow was greater in IVUS-uncrossable lesions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, our results may be useful for establishing an educational program for junior RA operators. Because many literatures regarding RA and imaging devices have been published 1,[3][4][5][6][7][8][9][10] , even junior RA operators may be able to select an appropriate burr size, RotaWire, and RA strategy as long as an imaging device can cross the lesion before RA. However, as we shown here, there were many lesions that an IVUS catheter cannot cross, and the incidence of slow flow was greater in IVUS-uncrossable lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many groups rigorously published research articles regarding RA with intravascular imaging devices 3 , 4 , 6 9 . Moreover, several review articles explain the interpretation of intravascular imaging findings in RA to facilitate use of imaging devices in RA 1 , 5 , 10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By utilizing this device with the rotational speed raging between 160,000 and 200,000 rpm they showed that minimum lumen area, maximum reverberation number, angle, and length increased post atherectomy, which indicates calcium modification. In addition newly visible perivascular tissue through previously solid calcium (indicating calcium fracture) was observed [25].…”
Section: Atherectomy and Other Novel Treatmentsmentioning
confidence: 99%
“…The VH-IVUS technique utilizes backscattered ultrasound RF signals to perform feature extraction to identify plaque development by power spectral processing, including Fourier transform, welch power spectrum, and autoregressive models. Although this method can classify the degree of plaque development and reconstruct tissue histological images similar to histopathological sections [5], [6], it still has limitations. For example, the recognition ability of borders in VH-IVUS images is poor, usually requires manual Calibrated and the image reconstruction time is longer.…”
Section: Introductionmentioning
confidence: 99%